205k views
25 votes
I don't understand this ​

I don't understand this ​-example-1
User Vinzcent
by
5.3k points

1 Answer

8 votes

Answer:


m = 3 √(12)


n = 6

Explanation:

n=1/2 of 12 according to the rule:

right triangle the side opposite the 30 degree angle is half the length of the hypotenuse.

so n=12/2=6

and now we will need Pythagorean theorem : the sum of the squares on the legs of a right triangle is equal to the square on the hypotenuse (the side opposite the right angle)—or, in familiar algebraic notation, a2 + b2 = c2.

so


{m}^(2) + {n}^(2) = {12}^(2)

now lets put numbers on formula


{m}^(2) + {6}^(2) = {12}^(2)

from this formula m=


m = \sqrt{ {12}^(2) - {6}^(2) } = √(144 - 36) = √(108) = 3 √(12)

User Andrew Pouliot
by
5.2k points